Controles semiativos e observador de estados não linear aplicados em suspensão veicular com amortecedor magneto-reológico - Oliveira, Fernando Emerenciano Nunes de (2017)
Proven, the passive vehicle suspension system is a reliable and cost-effective solution solution for both chassis and wheel vibration levels reduction and chassis acceleration levels reduction. Although this system is widely used in vehicles, it has the disadvantage that its parameters can not be modified according to the variations generated by the track. This results in the use of the active suspension system, which allows the variation of the parameters of the suspension in real time, however, the use of this type of suspension requires a high level of energy for the correct operation of its actuators, resulting in the unfeasibility of some applications. To solve the disadvantages found for the passive and active suspension system, the semiactive suspension system arises, which combines the advantages of the active system, but with a lower energy consumption, consequently generating a reliable and economical solution control option to the problems of maneuverability and vehicular comfort. The present work intends to perform two evaluations, the first being the evaluation and comparison of a passive suspension system with the performance of four semi-active controllers (on/off, skyhook, groundhook and hybrid) and the second is to test the same controllers, but considering the dynamics of a magneticrheological damper through the LuGre model. These controllers will be applied to a nonlinear model of a quarter-car with two degrees of freedom, with its variables being estimated through a nonlinear state observer. The analysis for the comparison of the systems will be performed through numerical simulations using MatLab® software. The simulations of the disturbances generated by the track will be performed through a step function and a pulse function in order to evaluate the performance of each controller. After the implementation of the control algorithms, it was possible to verify that the system of semi-active suspension against the proposed excitations presented a superior performance in relation to comfort. However, not as significant as comfort, the controllable system alo compared to the passive system, presented improvements in the steerability requirement.